TECHNOLOGY READINESS AND ACCEPTANCE PREDICT TAX AUDITORS’ DIGITAL ADOPTION - Asqolani, Asqolani; Priyono, Agus Praises (Kesatuan Press, 2025)
In recent developments, incorporating digital technologies into auditing practices has accelerated, notably through the widespread use of Computer-Assisted Audit Tools and Techniques (CAATs). However, the readiness of tax auditors to embrace these innovations varies considerably, shaped by individual psychological traits and attitudes toward technology. This study investigates how tax auditors’ technology readiness influences their perceptions and acceptance of CAATs within the Coretax implementation by the Directorate General of Taxes (DGT). This study combines the Technology Readiness Index (TRI) 2.0 with the Technology Acceptance Model (TAM) framework. Empirical data were obtained from 85 tax auditors across 13 offices within the DGT Banten area and examined using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that optimism significantly and positively influences perceived usefulness and ease of use. These perceptions subsequently play a crucial role in shaping the behavioral intention to implement CAATs. The study suggests that enhancing auditors' confidence and positive outlook toward technology adoption can foster greater acceptance of audit digitization tools. This research adds to the scarce body of empirical studies that merge TRI and TAM frameworks in public sector contexts, providing actionable perspectives on digital transformation in tax audit settings.